IMPLEMENTASI PERATURAN KERJA SAMA KEMITRAAN DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN KAWASAN KONSERVASI PADA BALAI KONSERVASI SUMBER DAYA ALAM KALIMANTAN SELATAN (STUDI KASUS DI CAGAR ALAM TELUK KELUMPANG, SELAT LAUT, SELAT SEBUKU - Franscisca Sekar Jayanti Manapa (Lambung Mangkurat University-Indonesia, 2021)
The collaborative and synergistic management of Teluk Kelumpang, Selat Laut, and Selat Sebuku Nature Reserve is carried out based on the mutual understanding and agreement of the stakeholders, in accordance with the prevailing laws and regulations and manifested in joint activities according to the principles of professionalism and accountability. This study aimed to assess the quality of the joint regulations, to assess the roles of the stakeholders in carrying out the collaborative efforts, to assess the collaborative process, and to assess the effectiveness of the management in Teluk Kelumpang, Selat Laut and Selat Sebuku Nature Reserve.This qualitative research used a descriptive method. It was done in Teluk Kelumpang, Selat Laut and Selat Sebuku Nature Reserve and Natural Resource Conservation Agency of South Kalimantan. The results revealed: first, the good quality of the joint regulation as indicated by the absence of conflict; the consistency; the accountability and promptness of the regulation. Second, the significance of the stakeholders role in the collaborative efforts in Teluk Kelumpang, Selat Laut, and Selat Sebuku Nature Reserve. The first and second players are the primary actors. Third, the collaboration in Teluk Kelumpang, Selat Laut, and Selat Sebuku Nature Reserve, is carried out based on the joint regulation. Fourth, the attainment of the threshold of the protected area management effectiveness is affected by the threats and weaknesses in areas. The issuance of joint regulation potentially diminishes the threats and weaknesses in area management, and eventually enhances the value of protected area management effectiveness. Based on these results, it is recommended: to issue regulation on the technical guidelines for the management of nature reserve and nature conservation areas and also to standardize the template for the documentation of collaborative management as the guideline/reference.